2019
DOI: 10.1186/s12884-019-2249-z
|View full text |Cite
|
Sign up to set email alerts
|

Maternal body mass index and risk of neonatal adverse outcomes in China: a systematic review and meta-analysis

Abstract: Background Maternal body mass index is linked to short- and long-term unfavorable health outcomes both for child and mother. We conducted a systematic review and meta-analysis of population-based cohort studies to evaluate maternal BMI and the risk of harmful neonatal outcomes in China. Methods Six databases identified 2454 articles; 46 met the inclusion criteria for this study. The dichotomous data on maternal BMI and harmful neonatal outcomes were extracted. Pooled st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
84
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 42 publications
(69 reference statements)
9
84
1
1
Order By: Relevance
“…Unlike the current study, previous research found preterm birth and LBW to be associated with other factors as well-for example, LBW with maternal age [12,45] and maternal BMI [45,46] and preterm birth with maternal age [4,14] and maternal BMI [14,46,47].…”
Section: Discussioncontrasting
confidence: 98%
“…Unlike the current study, previous research found preterm birth and LBW to be associated with other factors as well-for example, LBW with maternal age [12,45] and maternal BMI [45,46] and preterm birth with maternal age [4,14] and maternal BMI [14,46,47].…”
Section: Discussioncontrasting
confidence: 98%
“…Over the past few decades, overweight and obesity have become a growing health problem in the Western world [1], so much so that WHO now considers it one of the most relevant health problems [2]. The distribution of this problem is not homogeneous among the population, being women's rates higher than men's [3], and this makes obesity a problem that greatly affects women of reproductive age.…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental and epidemiological studies show that nutritional changes in the prenatal and postnatal stages of life can have a significant impact on the child's health and development [2,3,[7][8][9]. Maternal overweight, obesity, and morbid obesity are already known to be associated with adverse obstetric and neonatal outcomes [3,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, GDM affects 3-25% pregnancies, and the continued increase in the incidence of this disease is consistent with an increasing prevalence of obesity [7]. Both maternal obesity and GDM are independent risk factors for obstetric and neonatal complications, such as caesarean section, macrosomia, preeclampsia, or other metabolic disorders at multiple life stages in the offspring [8,9]. It seems, nonetheless, that obese women with GDM appear to have a higher risk of adverse outcomes than women who suffered from obesity alone or GDM alone [10,11].…”
Section: Introductionmentioning
confidence: 99%